The Analysis of Students’ Concept Comprehension Ability on the Application of CLIS Learning Models Integrated Ethnoscience (Journal of Primary Education, 2019)
This study aims to analyze the improvement of students' concept comprehension ability by applying CLIS (Children Learning In Science) learning models integrated ethnoscience. This study employed a quasi experimental method with one group pretest-posttest design. The data used include pretest and posttest score. The data were analyzed using the one-sample test for the average test, proportion test (Z test) to calculate the classical completeness and N-gain calculation. The result revealed that students who fulfill the minimum standard criteria (KKM) were 30 students with the classical completeness 93.75%. The proportion completeness of concept comprehension ability passed over 75%. The improvement of concept comprehension ability was 0.4 and categorized as medium. Each indicators of concept comprehension increased sequentially that is translating 86.3%, exemplifying 91%, classifying 77.5%, summarizing 76.3%, predicting 88.8% and explaining 73.8%. The improvement of indicator concept comprehension generally in the very good category. Based on the result obtained, it can be concluded that the application of CLIS learning models integrated ethnoscience can improve students’ concept comprehension.